2011
DOI: 10.1111/j.1751-9020.2011.00377.x
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile Courts and Competency to Stand Trial

Abstract: This article reviews the recent development of juvenile competency to stand trial (CST) policies across the United States in light of the inherent contradiction of this due process procedure in a separate juvenile court that is premised on the incompetence of youth. The article draws on existing CST legal doctrine and psycho‐legal research to demonstrate the need for sociolegal research to better understand who gains access to the CST process, CST decisions, and how CST may influence subsequent case processing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…For this reason, evaluators' concluding opinions (including ultimate-issue opinions and also conclusory penultimate statements) were used as the dependent variable of AC. Research has consistently found very high agreement between evaluator opinions and judicial determinations of competence (Harvey, 2011;Kruh et al, 2006;Zapf et al, 2004).…”
Section: The Present Studymentioning
confidence: 96%
See 1 more Smart Citation
“…For this reason, evaluators' concluding opinions (including ultimate-issue opinions and also conclusory penultimate statements) were used as the dependent variable of AC. Research has consistently found very high agreement between evaluator opinions and judicial determinations of competence (Harvey, 2011;Kruh et al, 2006;Zapf et al, 2004).…”
Section: The Present Studymentioning
confidence: 96%
“…Although competence became relevant to youth as due process protections were extended to the juvenile courts in the 1960s (In re Gault, 1967; Kent v. United States , 1966), it was not until the “get tough” era of the 1990s, when more and younger youth began facing more adversarial processes and punitive outcomes, that the question of competence was increasingly raised in the juvenile courts (Bonnie & Grisso, 2000; Grisso, 2003). Despite this increase, attorneys may not raise the question of competence as often as they have actual concerns about a youth’s AC (Viljoen et al, 2010), suggesting juvenile AC is neither appropriately nor sufficiently addressed (Bryant et al, 2015; Grossi et al, 2016; Harvey, 2011).…”
Section: Ac From Criminal To Juvenile Courtmentioning
confidence: 99%